KESALAHAN PENULISAN KATA PADA SPANDUK DI WILAYAH KOTA MEDAN - Mutiara Cahriza Nst; Saymay Br Tambunan; Afif Hafizha; Bagas Abdulla Hasymi; Afriza Ruby Yusuf; Suhariyanti Suhariyanti (Jurnal Dialect, 2025)
A banner is one example of a form of communication delivered in written form. However, it is possible that banner makers ignore the writing rules so that some writings on banners are found to be incorrect. This study aims to analyze spelling errors on banners in the Medan City area. The research method uses a qualitative approach. The results of the study showed that the most common spelling errors were spelling errors, use of foreign languages, and inappropriate word choices. The results of this study are expected to contribute to increasing awareness of the importance of using good and correct Indonesian.